Interactions between ionizing radiation and Vairimorpha (Nosema) ceranae on the honeybee, Apis mellifera L. - Margot Crevet; Béatrice Gagnaire; Jean-Marc Bonzom; Nicolas Dubourg; Michel Pélissier; Fabrice Daian; Gabriel Bon; Loïc Quevarec; Luc P. Belzunces; Jean-Luc Brunet (PLoS ONE, 2026)
The global decline of honeybee colonies represents a major ecological concern, primarily attributed to simultaneous exposure to multiple stressors. These include biotic pressures, such as parasitic infections, and abiotic pressures, such as exposure to ionizing radiation, which remains poorly understood. Assessing their combined effects provides novel insights into how biological and radiological stressors interact within the organism. Here, we investigated the individual and combined effects of Vairimorpha ceranae (formerly Nosema ceranae ) infection and chronic gamma irradiation (14 µGy/h or 14 × 10³ µGy/h) on honeybee health. Measurements included survival, syrup consumption, spore load, and biomarkers related to energy metabolism, antioxidant defenses, immunity, detoxification, and neural enzyme activity. Two successive experiments, conducted at different collection periods, allowed us to account for biological variability between bee cohorts. Infection by V. ceranae caused high mortality and major impairments in metabolic, antioxidant, and immune functions. Ionizing radiation induced more moderate effects, characterized by redox imbalance and reduced detoxification capacity, which varied with dose rate. Under combined exposure, the two stressors produced mainly antagonistic interactions affecting antioxidant, immune, and detoxification systems. However, a synergistic effect was observed on ATP production, suggesting an energetic compensation mechanism. These findings highlight complex physiological disturbances, revealing the multifactorial vulnerability of honeybees and emphasizing the need to integrate interactions between multiple stressors and natural biological variability into ecotoxicological assessments.